2016
DOI: 10.1515/mgrsd-2015-0016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Imaging Spectroscopy for rock identification in the Karkonosze Mountains, Poland

Abstract: Based on laboratory, field and airborne-acquired hyperspectral data, this paper aims to analyse the dominant minerals and rocks found in the Polish Karkonosze Mountains. Laboratory spectral characteristics were measured with the ASD FieldSpec 3 spectrometer and images were obtained from VITO’s Airborne Prism EXperiment (APEX) scanner. The terrain is covered mainly by lichens or vascular plants creating significant difficulties for rock identification. However, hyperspectral airborne imagery allowed for subpixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The field data were acquired during an in situ measurement campaign between 4 and 7 August 2015 using an ASD FieldSpec 3 spectroradiometer (ASD Inc., Longmont, CO, USA, Table 1) fit with an ASD PlantProbe [36]. The contact probe, which uses an artificial light and closed chamber for data Data were acquired from seven sites on dry to moist tundra communities dominated by the vascular species mentioned above ( Figure 1).…”
Section: In-situ Data Collection and Processingmentioning
confidence: 99%
“…The field data were acquired during an in situ measurement campaign between 4 and 7 August 2015 using an ASD FieldSpec 3 spectroradiometer (ASD Inc., Longmont, CO, USA, Table 1) fit with an ASD PlantProbe [36]. The contact probe, which uses an artificial light and closed chamber for data Data were acquired from seven sites on dry to moist tundra communities dominated by the vascular species mentioned above ( Figure 1).…”
Section: In-situ Data Collection and Processingmentioning
confidence: 99%
“…e spectral variability of similar rocks types was examined by Mierczyk et al [31] which found an overall accuracy of 63.5% using SAM. Schneider et al [48] compared laboratory and field spectral images using several classification methods and found differences in the performance due to illumination conditions, calibration approach, and the presence of dust deposits.…”
Section: E Feasibility Of Classifying the Rocks Samplesmentioning
confidence: 99%
“…e identification and classification of rocks and minerals have been the focus in many studies either by using their spectral characteristics [30] or by various spectral processing methods such as spectral angle mapper (SAM) [10,[31][32][33], support vector machines (SVM) [32,34], and principal component analysis (PCA) [35]. Recent studies found an overall classification accuracy of 66% based on the spectral data of various rocks [36] and an accuracy of 67.4% and 69.7% based on SAM and spectral information divergence (SID), respectively [37].…”
Section: Introductionmentioning
confidence: 99%
“…The wealth of spectral information available from advanced hyperspectral imaging instruments has opened new perspectives in many application domains. For example, monitoring of natural grasslands and the synanthropic patterns of invasive species [1], mapping of tree species in a complex mixed forest ecosystem [2] and analyzing the dominant minerals and rocks in a mountain region [3], mapping and estimation of the amounts of hazardous materials to human health [4] and urban land-cover mapping with high resolution images [5] are among others. Besides, retrieving the atmospheric condition parameters aid to the atmospheric correction and the atmosphere monitoring processes.…”
Section: Introductionmentioning
confidence: 99%